Alteration in human defensin-5 expression following gastric bypass surgery. Issue 9 (5th April 2007) - Sundbom, M; Elphick, D A; Mahida, Y R; Cunliffe, R N; Midtvedt, T; Engstrand, L; Rubio, C; Axelsson, L Göran
Abstract : Background: Roux-en-Y gastric bypass surgery provides a novel human model to investigate small bowel mucosal innate immunity, in which there is loss of gastric acid-mediated protection against orally-acquired microorganisms. Aim: To study changes in jejunal mucosal immunoreactivity of human defensin (HD)-5, an antimicrobial peptide normally produced by Paneth cells. Methods: Mucosal samples were obtained from 18 female patients (24–54 years), from the same segment of jejunum during and after gastric bypass surgery. Samples were used for bacterial culture and immunohistochemistry using anti-HD-5 antibody. The number of immunoreactive cells per crypt and villus were determined and expressed as mean (SD). Results: No bacteria were cultured from any of the perioperative jejunal samples but colonies of bacteria normally present in the pharynx were identified during culture of all postoperative jejunal biopsy specimens (1–>100 colonies). Paneth cell numbers per crypt were unchanged after gastric bypass (4.16 (0.71) vs 4.24 (0.78)). However, following surgery, there was an increase in HD-5-positive intermediate cells per crypt (0.25 (0.41) vs 1.12 (0.66), p<0.01), HD-5 staining enterocytes per crypt (0.03 (0.09) vs 1.38 (1.10), p<0.01), HD-5 staining material in the crypt lumen (crypt lumens: 5.0% (10.9%) vs 68.1% (27.9%), p<0.01) and HD-5 immunoreactivity coating the luminal surface of villus enterocytes (villi sampled: 15.0% (31.0%) vs 67.5% (42.0%), p<0.01). Conclusions: Bacteria normally resident in the pharynx were present in the proximal jejunal mucosa following Roux-en-Y gastric bypass surgery. After gastric bypass, there was increased secretion of HD-5 and an increase in HD-5 expressing intermediate cells and enterocytes in the crypt. The increase in HD-5 expression in the jejunal mucosa following gastric bypass surgery is likely to be secondary to exposure to orally-acquired microorganisms.